Molecular Dynamics Study for Inhibition of Iron Corrosion in High-Temperature Liquid PbBi with Nobel Gas Inhibitors - Sa’adah, Umi; Arkundato, Artoto; Rohman, Lutfi (Jurnal ILMU DASAR, 2016)
Molecular dynamics is a popular method to observe the movement of interacting molecules. In this study molecular dynamics method was used to observe the phenomenon of iron corrosion and analyze effect of noble gases as a corrosion inhibitor for iron in liquid metal PbBi. Physical quantities are evaluated from the results of this study including: Mean Square Displacement (MSD), the diffusion coefficient, and for the crystal structure is visualized using Ovito program. The ron is placed in the middle high temperature liquid PbBi, the noble gases is injected into the liquid metal. Based on the three kinds of the noble gases (helium, neon, and argon) thhat injected into the molten metal PbBi, it obtained that Argon is the most effective in inhibiting the corrosion of iron. Argon is able to reduce the corrosion rate of 80.29% iron for temperature of 1023K. One reason to use the noble gas because these gases are difficult to react with other elements. Keywords: Molecular Dynamics, Corrosion in Liquid metals, Nobel Gases, Inhibitors